Vitamin C influences antioxidative, anti-inflammatory and wound healing markers in smokers' gingival fibroblasts in vitro - Ruaa Alyami; Reham Al Jasser; Fahad Ali Alshehri; Nouf Alshibani; Sarah Bin Hamdan; Riham Abdulaziz Alyami; Abdurahman A. Niazy (Elsevier, 2023)
Background: Saudi Arabia has an overall smoking rate of 15.9%. The link between smoking and periodontal disease has been studied extensively. It is possible for human gingival fibroblasts to accumulate nicotine intracellularly over a period of four hours. Additionally, unmetabolized nicotine is released into the environment. Tobacco presence can impair tissue inflammation, wound healing, and organ development. To counterbalance tobacco toxins, vitamin C has been added to a variety of products. Aim: This study aims to analyze the RNA expression of antioxidant, anti-inflammatory, and wound healing proteins in human gingival fibroblasts from smokers and nonsmokers using polymerase chain reaction. Materials and Methods: hGFs were extracted from clinically healthy periodontium sites of adult male subjects. Both heavy cigarette smokers and never-smokers participated as subjects. Cells were cultured and subcultured in supplemented growth medium. Vitamin C was inducted in the medium at the experimental 6th passage. RNA expression analysis (qRT-PCR) was performed to analyze adhesion, proliferation, and extracellular matrix expression. Results: The results revealed marked expression of a wound healing gene (VEGF-A) in never-smokers (p value = 0.016). GPX3 and SOD3 represent antioxidants that are highly expressed in treated never-smoker cells. SOD2 significantly increased (p value = 0.016) in smokers after vitamin C exposure. The anti-inflammatory markers IL-6 and IL-8 were lower among smokers than among nonsmokers (p < 0.0001). Conclusion: Tobacco smoking suppressed gingival fibroblasts' abilities to regenerate, heal, combat inflammation, and resist free radicals. Vitamin C at cellular levels was beneficial and should be considered in the treatment component of smokers in the dental clinic.